Utilizing google cardboard virtual reality for visualization in multivariable calculus - Cheong, Kang Hao (2023)
In this study, we have developed a webXR tool that helps students visualise 3D graphs from functions of two variables through the use of simple, practical and cost-effective Google Cardboard for use in the classroom. Further, we have assessed Google Cardboard’s usability as a content delivery system in a mid-sized multivariable calculus classroom with about 40 students and about 40 other students in the control group. We also assess if Google Cardboard is better than PowerPoint slides, shown on flat screen computers, in terms of students’ attitudes and engagement towards the teaching and learning of multivariable calculus. Our results reveal that Google Cardboard functions better than PowerPoint slides when encouraging students’ attitudes and engagement towards learning multivariable calculus. At the same time, Google Cardboard as a content delivery system does not appear to differ from PowerPoint slides in terms of its usability.